1997
DOI: 10.1007/s001070050240
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Ermittlung der Bruchzähigkeit and MDF-Platten

Abstract: Determination of the fracture toughness of MDF hoardFracture toughness is a measure for the crack resistance of a material. This paper presents the results of an analysis on the infuence of density and moisture content on fracture toughness of MDF. Fracture toughness was measured using ASTM E 399 with CT-specimens (parallel to the board direction). Acoustic emission analysis and scanning electron microscopy (SEM) were used to assess the kind of fracture and the fracture surface. Higher fracture toughness value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
(1 reference statement)
0
9
1
Order By: Relevance
“…Which of the two concepts is applied depends on the relationship of process zone and the specimen geometry. In terms of wood, LEFM is known and widely used (Porter 1964, Patton-Mallory and Cramer 1987, Valentin and Adjanohoun 1992, Niemz et al 1997, Niemz and Diener 1999. The usage of wood as a testing material and the knowledge about its non-isotropic material characteristics makes small sized specimens questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Which of the two concepts is applied depends on the relationship of process zone and the specimen geometry. In terms of wood, LEFM is known and widely used (Porter 1964, Patton-Mallory and Cramer 1987, Valentin and Adjanohoun 1992, Niemz et al 1997, Niemz and Diener 1999. The usage of wood as a testing material and the knowledge about its non-isotropic material characteristics makes small sized specimens questionable.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies investigates the fracture toughness of PB [8][9][10]. The same like in the case of MDF, different values of fracture toughness were obtained: Matsumoto and Nairn [11] 2.57 MPa•m 1/2 for density of 609 kg/m 3 , respectively 3.77 MPa•m 1/2 for density of 769 kg/m 3 using Compact Tension (CT) specimens, while for wedge splitting specimens and a density of 710 kg/m 3 Niemz et al [12] obtained 1.81 MPa•m 1/2 . Fewer investigations were carried out on mixed mode fracture toughness of PB and MDF, [13].…”
Section: Introductionmentioning
confidence: 75%
“…Only a few experiments analyzing the fracture toughness of MDF were found in the literature. Niemz et al , [ 23 , 24 ] used CT specimens according to ASTM 399 to analyze the stress intensity factor. The specimens were oriented parallel to the board plane and yielded K IC values of 1.81 ± 0.33 MPam 0.5 (CV 18.2%) for a density of 710 kg/m 3 (20 °C/65% RH) and numbers in a range of 0.36 ± 0.03 MPam 0.5 (8.3% CV) to 1.29 ± 0.06 MPam 0.5 (CV 4.7%) with a density of 500 kg/m 3 , depending on the equilibrium moisture content, which varied from 21.4% to 3.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is reported that wood [ 5 ] and wood based panels [ 6 , 7 ] show non-linear characteristics, which is due to the large process zone and fiber bridging, nevertheless the concept of linear fracture mechanics for measuring toughness is widely accepted [ 5 , 15 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%